2017
DOI: 10.1051/mmnp/201712508
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation Analysis of a Modified Tumor-immune System Interaction Model Involving Time Delay

Abstract: We study stability and Hopf bifurcation analysis of a model that refers to the competition between the immune system and an aggressive host such as a tumor. The model which describes this competition is governed by a reaction-diffusion system including time delay under the Neumann boundary conditions, and is based on Kuznetsov-Taylor's model. Choosing the delay parameter as a bifurcation parameter, we first show that Hopf bifurcation occurs. Second, we determine two properties of the periodic solution, namely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…We have noticed that during tumor proliferation, there is usually a period of latency. Many studies have shown that time delays can disrupt the homeostasis of the human immune system and lead to altered stability (Kayan et al, 2017;Banerjee et al, 2008). Therefore, considering the time delay factor in tumor immune models better reflects the objective pattern and has important scientific significance.…”
Section: Introductionmentioning
confidence: 99%
“…We have noticed that during tumor proliferation, there is usually a period of latency. Many studies have shown that time delays can disrupt the homeostasis of the human immune system and lead to altered stability (Kayan et al, 2017;Banerjee et al, 2008). Therefore, considering the time delay factor in tumor immune models better reflects the objective pattern and has important scientific significance.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that uniform activation of helper T -cells can help in ECs stimulation and tumor control. Considering a reaction-diffusion system, including time delay under the Neumann boundary conditions, Kayan et al [ 30 ] modified the model [ 11 ] which described tumor-immune competitions. They studied the Hopf bifurcation analysis and found that the effect of diffusion of tumor-immune interaction can significantly change the dynamics of the model.…”
Section: Introductionmentioning
confidence: 99%